Changes in Contributions of Swimming, Cycling, and Running Performances on Overall Triathlon Performance Over a 26-Year Period. Issue 9 (September 2016) - Figueiredo, Pedro; Marques, Elisa A.; Lepers, Romuald
Abstract : Abstract: Figueiredo, P, Marques, EA, and Lepers, R. Changes in contributions of swimming, cycling, and running performances on overall triathlon performance over a 26-year period. J Strength Cond Res 30(9): 2406–2415, 2016—This study examined the changes in the individual contribution of each discipline to the overall performance of Olympic and Ironman distance triathlons among men and women. Between 1989 and 2014, overall performances and their component disciplines (swimming, cycling and running) were analyzed from the top 50 overall male and female finishers. Regression analyses determined that for the Olympic distance, the split times in swimming and running decreased over the years ( r 2 = 0.25–0.43, p ⩽ 0.05), whereas the cycling split and total time remained unchanged ( p > 0.05), for both sexes. For the Ironman distance, the cycling and running splits and the total time decreased ( r 2 = 0.19–0.88, p ⩽ 0.05), whereas swimming time remained stable, for both men and women. The average contribution of the swimming stage (∼18%) was smaller than the cycling and running stages ( p ⩽ 0.05), for both distances and both sexes. Running (∼47%) and then cycling (∼36%) had the greatest contribution to overall performance for the Olympic distance (∼47%), whereas for the Ironman distance, cycling and running presented similar contributions (∼40%, p > 0.05). Across the years, in the Olympic distance, swimming contribution significantly decreased for women and men ( r 2 = 0.51 and 0.68, p < 0.001, respectively), whereas running increased for men ( r 2 = 0.33, p = 0.014). In the Ironman distance, swimming and cycling contributions changed in an undulating fashion, being inverse between the two segments, for both sexes ( p < 0.01), whereas running contribution decreased for men only ( r 2 = 0.61, p = 0.001). These findings highlight that strategies to improve running performance should be the main focus on the preparation to compete in the Olympic distance; whereas, in the Ironman, both cycling and running are decisive and should be well developed.